Determinants of establishment success: Comparing alien and native freshwater fishes in Taiwan - Liang, Shih-Hsiung (PLoS One, 2020)
Many parts of Asia, including Taiwan, have suffered severely from freshwater fish invasions. However, few studies using an assemblage approach have been conducted in the region so far that would help to prioritize suitable preventive actions. In this study, we focused on the invasion process from the import stage to the establishment stage, and defined establishment success as the success during this predefined process. We used datasets of freshwater fish assemblages in Taiwan to (1) compare established versus non-established alien species to distinguish the determinants of establishment success, and (2) to use these determinants to test a life history hypothesis which predicts that the magnitudes of the determinants should be significantly different between established alien species and native species. We collated a dataset for freshwater fish species which were imported into Taiwan (n = 118) of which some successfully established (n = 26), and another dataset for freshwater fish species native to Taiwan (n = 77). For each imported species, we collected data for 17 variables, including two phylogenetic, two human-use, two invasion history, and 11 life history variables. We then used decision tree methods, which have advantages in analyzing datasets with many variables of mixed types without the need to make assumptions about data distributions and input data for missing values. Our results showed that aquaculture use and maximum body length were the most important determinants for predicting establishment success of alien freshwater fish in Taiwan. Comparing five important determinants between established alien versus native species showed that the established alien species were significantly more often used in aquaculture, were associated with a higher number of established countries, and had a larger body length and greater highest water temperature tolerance than the native species. We thus conclude that our results provided evidence to support our stated hypothesis. We suggest that aquaculture use, measures of body size, and the number of previously invaded countries may alert researchers and conservation managers to species with a high establishment potential, especially for countries with similar conditions as those in Taiwan.